Clinical Efficacy of Gemifloxacin-containing Triple Therapy for First-line Treatment of Helicobacter pylori Infection: A Pilot Study - Tae Jun Kim; Jeung Hui Pyo; Hyuk Lee; Yang Won Min; Byung-Hoon Min; Jun Haeng Lee; Jae J. Kim (Yong Chan Lee, 2017)
Background/Aims: Levofloxacin resistance is increasing rapidly, and widely limits its application in Helicobacter pylori eradication. This study aimed to evaluate the efficacy of a clarithromycin- versus gemifloxacin-containing triple therapy regimen in first-line eradication of H. pylori infection. Materials and Methods: This was an open-label, prospective, non-randomized two-armed pilot study in which treatment-naïve subjects with active H. pylori infection received a seven-day triple therapy with rabeprazole 20 mg bid (twice daily), gemifloxacin 320 mg qd (once daily), and amoxicillin 500 mg bid (n=70) or seven-day triple therapy with rabeprazole 20 mg bid (twice daily), clarithromycin 500 mg bid (twice daily), and amoxicillin 500 mg bid (n=83). H. pylori infection status was checked in all patients at enrollment and at least 8 weeks after the end of therapy by the urea breath test. Results: Intention-to-treat eradication rates were 71.1% and 74.3% for clarithromycin-containing triple therapy and gemifloxacin-containing triple therapy, respectively (P=0.398). The corresponding per-protocol eradication rates were 76.6% and 76.1% (P=0.624). The gemifloxacin-containing triple therapy was associated with a lower incidence of adverse events (2.9% vs. 18.5%, P=0.003). Conclusions: Although the seven-day gemifloxacin-containing triple therapy regimen showed a more favorable safety profile, there was no significant difference in eradication rates between the gemifloxacin-containing and clarithromycin-containing triple regimens, and both regimens had eradication rates slightly lower than acceptable efficacy for the Korean population. Therefore, the gemifloxacin-containing regimen might be useful as an alternative regimen for patients showing severe side effects of clarithromycin due to poor tolerance. Further studies on the efficacy of gemifloxacin in the Korean population are warranted.